Cortical time course of object naming investigated by repetitive navigated transcranial magnetic stimulation. - Sollmann, Nico; Ille, Sebastian; Negwer, Chiara; Boeckh-Behrens, Tobias; Ringel, Florian; Meyer, Bernhard; Krieg, Sandro; Krieg, Sandro M (Brain Imaging & Behavior, 2017)
Human language organization models and language time course patterns are still predominantly derived from meta-analyses of numerous single publications, which only investigated scattered cortical regions. Moreover, there is not much literature available on the exact impact of repetitive navigated transcranial magnetic stimulation (rTMS) onset times on object naming. We, therefore, used a virtual lesion-based approach by mapping various cortical areas with rTMS to investigate the time course of object naming, and to specifically provide data on the pattern of rTMS language mapping results depending on different stimulation onset times. Ten healthy, right-handed subjects were enrolled, and rTMS in combination with an object-naming task was performed with different stimulation onset times (0 ms, 100 ms, 200 ms, 300 ms, 400 ms, and 500 ms). Subsequent to language mapping, all naming errors detected were systematically classified with respect to previous literature. The majority of errors was elicited within the opercular inferior frontal gyrus (opIFG) and ventral precentral gyrus (vPrG), and the spatial distribution of naming errors changed according to the time point of naming disruption by varying onset times. For instance, immediate rTMS onset led to a widespread cortical distribution of no responses, whereas performance and hesitation errors increased with higher stimulation onset times.